The Long-Run Impacts of Same-Race Teachers - Seth Gershenson; Cassandra M. D. Hart; Constance A. Lindsay; Nicholas W. Papageorge (Institute of Labor Economics (IZA), 2017)
Black primary-school students matched to a same-race teacher perform better on standardized tests and face more favorable teacher perceptions, yet little is known about the long-run, sustained impacts of student-teacher demographic match. We show that assigning a black male to a black teacher in the third, fourth, or fifth grades significantly reduces the probability that he drops out of high school, particularly among the most economically disadvantaged black males. Exposure to at least one black teacher in grades 3-5 also increases the likelihood that persistently low-income students of both sexes aspire to attend a four-year college. These findings are robust across administrative data from two states and multiple identification strategies, including an instrumental variables strategy that exploits within-school, intertemporal variation in the proportion of black teachers, family fixed-effects models that compare siblings who attended the same school, and the random assignment of students and teachers to classrooms created by the Project STAR class-size reduction experiment.
Keywords: I2; 330; teachers; long-run effects; educational attainment; racial gaps